Software testing : a craftsman's approach - Jorgensen, Paul. (Boca Raton, [Florida] : CRC Press, Taylor & Francis Group, 2014)
"The fourth edition of the widely adopted text and reference book is completely revised and updated and features a new section on Life Cycle-Based Testing. New chapters cover Software Complexity and Mutation Testing and Error Seeding. The text still provides a solid mathematical background in discrete mathematics and linear graph theory that is fundamental to understating software testing. The book also describes specification-based (functional) and code-based (structural) test development techniques, while extending this theoretical approach to less understood levels of integration and system testing"--
Incluye referencias bibliográficas, apéndice e índice.
Keywords: Computer software -- Testing; COMPUTERS / Information Technology; COMPUTERS / Programming Languages / General; COMPUTERS / Software Development & Engineering / General